PENERAPAN MODEL THINK PAIR SHARE UNTUK MENINGKATKAN HASIL BELAJAR MATERI PENYAJIAN DATA DI KELAS IV SDN 11 PAUH KOTA PADANG - Rizky Kusuma, Wini; Melva Zainil; MasnilaDevi; Desyandri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to improve students’ mathematics learning outcomes on datapresentation material through the implementation of the Think Pair Share (TPS)learning model in Grade V students of SDN II Pauh. The background of this studywas based on the low learning outcomes of students in interpreting and concludingdata. Students still experienced difficulties in reading tables and diagrams, analyzingdata, and drawing conclusions from the presented data. This research usedClassroom Action Research (CAR) consisting of two cycles, where each cycleincluded planning, implementation, observation, and reflection stages. The subjectsof this study were Grade V students of SDN II Pauh. Data collection techniques usedobservation, tests, and documentation. The results showed that the implementationof the Think Pair Share (TPS) model could improve students’ learning outcomes.This improvement was evident from the increase in teacher activity, student activity,and learning outcomes in each cycle. Students became more active in discussions,more confident in presenting their ideas, and more capable of interpreting andconcluding data correctly. Therefore, the Think Pair Share (TPS) model can be usedas an alternative learning model to improve mathematics learning outcomes inelementary schools.